Function mechanism of porous bed absorbing hazardous ultra-fined particles during iron ore sintering process. (25th November 2020) - Ji, Zhiyun; Huang, Binbin; Gan, Min; Fan, Xiaohui; Chen, Xuling
ABSTRACT: This study revealed the relationship between the emission profile of PM10 & PM2.5 and absorption property of porous sintering bed, and elucidated the potential mechanism. Results show that both PM10 and PM2.5 characterized regionally high emission property, and tended to be higher from stage-4 to stage-6 for PM10 and from stage-4 to stage-5 for PM2.5 . Increasing the wet mixture layer thickness and moisture content improved the absorption efficiency to PM10 and PM2.5 . Potential absorption mechanism can be mainly attributed to the inertial effect and condensed water vapour agglomeration effect in porous sintering bed. Stage-1 to stage-3 corresponded to thicker wet porous particle layer, and stronger agglomeration effect of condensed water vapour, which made the sintering bed of stronger absorption capacity. Since wet mixture disappeared during stage-4 to stage-6, the absorption efficiency of sintering bed to PM10 and PM2.5 was weak, leading to their regional high emission concentration property.